(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This article has no abstract. The first 100 words appear below: A 4-year-old boy presenting with constipation for 1 month of his age. He used to defecate 3-4 days interval with rectal stimulation. The stool was semisolid, ribbon-like, and not associated with abdominal or perianal pain. He had a history of delayed passage of meconium. There was no history of the delayed developmental milestones. He received several medications including lactulose, magnesium hydroxide but there was a poor response. On examination, he was mildly pale, with no facial dysmorphism, anthropometrically well thrived. The back and spine were normal. There was no thyroid swelling. The skin was normal. The tone and jerk of lower limbs were normal.